‘송백(松柏)’과 ‘세한(歲寒)’ 도상 출현과 의미의 변화 - 김정희 <세한도(歲寒圖)> 연구 I - 김현권; Kim Hyun-kwon (인문학연구, 2021)
<세한도(歲寒圖)>는 김정희(金正喜, 1786-1856)가 제주유배 시절에 제자인 역관 이상적(李尙迪, 1804-1865)에게 그려 준 회화이다. 그는 이 작품에 『논어(論語)』의 「자한(子罕)」편을 조형화시켰으며 송(松)과 백(柏)을 제재로 사용하였다. 공자가 활동한 춘추시대에 송백(松柏)은 유학과 도가, 그리고 민간에서 여러 상징으로 이해되었으며 이 중에는 성현이나 곧은 성품을 칭송하는 경우가 많았다. 이 송백이 회화로 등장한 시기는 4세기 후반경이다. 특히 두 나무는 산수의 소재로 이용되므로 산수화 역사와 밀접하게 관련되기도 한다. 동아시아에서 산수화의 발생에는 불교 신자인 종병(宗炳, 375-443)에 의해 시작될 정도로 도가의 매카니즘을 이용하고 수용하면서 실재론의 성향을 띠는 동아시아 불교의 역할이 컸다. 8-9세기에 이르면 김정희의 <세한도>와 관련된 송백(松柏), 세한(歲寒), 쌍송(雙松)을 포함한 쌍수(雙樹), 그리고 언송(偃松) 요소가 산수화 속에 빈번하게 등장하였으며, 이후 오대 및 북송 초에는 위의 요소가 표현되는 것은 물론이고 화제로 사용되는 예가 상당히 증가한다. 그래서 이 시기 산수화에 보이는 나무의 도상은 김정희의 <세한도> 속 송백의 원형으로 거론되는 편이다. 그러나 오대 및 북송 초 산수화는 전경성이 강한 대관산수 화인 반면에 김정희의 <세한도>는 제재가 부각된 소경산수화이면서도 경물이 절제되어 있다. 더구나 전자에 표현된 개개 사물은 대자연의 일부 요소일 뿐으로, 유학, 도가, 불교라는 동아시아 사상의 상호 침투 현상 속에서 도가가 융합된 동아시아 불교와 연관된다면, 후자의 두 나무는 작가의 심리가 투영된 사물로, 도가와 불교의 자극과 영향 속에 발생한 신유학의 발생과 관련된다. 즉 김정희의 <세한도> 구성 형식의 일부는 소식과 주변의 화가들이 보여준, 자연과 사물의 모습을 심미적이고 주관적으로 파악하면서 상징성을 부여하고 그 의미를 강조하는 고목죽석도와 연관된다. < Sehan-do(Wintry days, 세한도, 歲寒圖) > is a painting drawn by Kim Junghee(김정희, 1786-1856) to give to his disciple Yi Sangjeok(이상적, 1804-1865) during his exile in Jeju. Kim Junghee used ‘Pine and Cypress(松柏)’ as sanctions to express the Lunyu(Analects of Confucius, 論語)-chapter Zihan(子罕). From the Spring and Autumn(春秋) Period when Confucius was active to the 4th Century, ‘Pine and Cypress’ was understood as a symbol of various things in Confucianism, Daoism, and the private sector, Likewise, there were a lot of cases praising saints among them. Later, ‘Pine and Cypress’ began to appear in paintings. In particular, the two trees are also used as subject matter for landscape paintings, Thus the flow of this material is closely related to the history of landscape painting. Just as landscape painting was initiated by a Buddhist believer Zong Bing(宗炳, 375-443), East Asian Buddhism which adopted Taoism and took on Naive Realism, played a crucial role in the creation of landscape painting. In the 8th and 9th centuries, ‘Pine and Cypress’, ‘Sehan’, ‘Twin Tree(雙樹)’ including ‘Twin Pine(雙松)’, and ‘Lying Pine Tree(偃松)’ began to appear frequently in landscape paintings. Afterward, in the Five Dynasties(五代) and the early Northern Song(北宋) Dynasty, these elements not only expressed in paintings but also used as titles of paintings increased considerably. Therefore, the icon of a tree in landscape paintings during this period is often discussed as the archetype of ‘Pine and Cypress’ in Kim Junghee’s < Sehan-do >. However, the landscape paintings of the Five dynasties(五代) and the early Northern Song(北宋) Dynasty are ‘Monumental-view landscape painting(大觀山水畵)’ with a strong panoramic propensity, whereas Kim Junghee’s < Saehan-do > is ‘Intimate-scene landscape painting(小景山水畵)’ with emphasis on sanctions. Moreover, the individual objects expressed in the former are only a part of nature and are directly related to East Asian Buddhism which combines Daoism. On the other hand, later two trees and house objects are projected into the artist’s psychology. Therefore, this is also related to Neo-Confucianism arising from the stimulation, influenced by Taoism and Buddhism. Comparatively, Some of Kim Junghee’s < Sehan-do > composition forms are related to the form of ‘Gomokjukseok-do(Dry tree-Bamboo-Stone Painting, 枯木竹石圖)’, painted by Sushi(蘇軾, 1036-1101) and his surrounding artists. This is because Kim Jeong-hee and sushi have a common point of understanding nature and objects aesthetically and subjectively, and giving them symbolism. It is vague to directly compare works such as Sushi and Kim Junghee’s < Sehan-do >, since there are development and change in East Asian painting between these two works.